Hesperidin related apoptosis on brain glioblastoma (Annals of Medical Research, 2021)
Aim: Even though the rate of brain glioblastoma tumors increases at the ages between 50 and 60, these tumors may occur at any age. Understanding of the molecular mechanisms which play role in the progress of this cancer type may lead to develop more effective strategies for a target driven therapy. Hesperidin is a herbal flavonoid which has anti-inflammatory and anti-oxidant effects that have been proven by different experiments. Also, there is no research in the literature that shows Hesperidin’s anti-proliferative and anti-apoptotic effect on glioblastoma tumors.Material and Methods: In this study, Hesperidin’s potential effects on brain glioblastoma tumor treatment was studied by using U-87 cell line. Hesperidin`s dosage effects on cell proliferation and vitality were measured by WST-1, and mitochondrial membrane potential was measured by JC-1. Also Caspase 3/BCA activity was measured.Results: 10 uM and 25 uM hesperidin treatment were resulted disruption of mitochondrial membrane potential (46% with 10 uM and 28% with 25 uM) with different caspase pathway in the light of viability ratio,10 uM hesperidin 32,6% and 25 uM hesperidin 25% alive cell on 48h incubation period. Conclusion: Our study, which will be the first one in the literature that indicates Hesperidin’s anti-apoptotic and anti-proliferative effect, has an original value. The values we will obtain will create new work fields, especially for cancer treatment and will contribute to science by becoming a new treatment option for brain glioblastoma tumors.